Prevalence of depression in patients referred with snoring and obstructive sleep apnoea. Issue 6 (9th June 2013) - Douglas, N.; Young, A.; Roebuck, T.; Ho, S.; Miller, B. R.; Kee, K.; Dabscheck, E. J.; Naughton, M. T.
Abstract Background and Aims Depression and obstructive sleep apnoea are two common entities, with common symptoms that make identification of either condition difficult. Our aim was to examine, within a group of patients referred with snoring and obstructive sleep apnoea, (i) the prevalence of depression with the 14‐question Hospital Anxiety and Depression Scale (HADS), (ii) the correlation between the two lead depression symptoms from the Mini‐International Neuropsychiatric Interview (MINI) and HADS, and (iii) the relationship between depression symptoms with physiological markers of OSA. Methods An observational study of depression questionnaires in patients referred because of snoring to a sleep clinic within university‐affiliated public teaching hospital. Results Ninety‐seven per cent of 240 patients approached responded, and 32% had a positive HADS (score >16/42). The HADS and MINI significantly correlated (r = 0.736, P < 0.001). Fifty‐three per cent had either doctor‐diagnosed depression (28%) and/or a positive HADS or MINI (25%). HADS correlated with the degree of sleepiness (r = 0.252, P < 0.0001) and inversely with hypoxaemia (r=‐0.231, P < 0.0003) but not with the frequency of apnoeas and hypopnoeas (r = 0.116, P > 0.05). Conclusion Depending on classification, 32–53% of patients with snoring had depressive symptoms or were on treatment, which is significantly greater than the Australian average of 21%. A simplified depression questionnaire was validated. Severity of depression correlated with sleepiness and hypoxaemia but not with severity of sleep apnoea.